Effect of continuous positive airway pressure on glucose metabolism in adults with type 2 diabetes: a systematic review and meta-analysis of randomized controlled trials - Zhu B. (2017)
© 2017 Springer International Publishing AG Obstructive sleep apnea (OSA) has many serious consequences, and one of these may be the exacerbation of type 2 diabetes mellitus (T2DM). Reports on the effect of continuous positive airway pressure (CPAP) on glucose metabolism in people with T2DM and OSA are conflicting. Therefore, the purpose of this review was to examine the effect of CPAP treatment on glucose metabolism by synthesizing findings from randomized controlled trials. The PRISMA review protocol was developed and registered in PROSPERO. A systematic search of PubMed, CINAHL, Embase, Web of Science, PsycInfo, and Cochrane was conducted from inception to March 2017. The Cochrane risk of bias tool was used to assess the study quality. Review Manager (v5.2) was used for the meta-analyses, and the standardized mean difference was calculated. Six studies consisting of 496 participants were included in this review. The meta-analyses indicated that CPAP treatment did not have significant impact on glucose metabolism measured by A1C (mean difference = 0.05, 95% CI − 0.14 to 0.24, P = 0.61), fasting insulin level (mean difference = − 2.34, 95% CI − 8.19 to 3.51, P = 0.43), and fasting glucose (mean difference = − 0.05, 95% CI − 0.52 to 0.42, P = 0.84). As expected, CPAP treatment can improve daytime sleepiness (mean difference = − 2.68, 95% CI − 3.91 to − 1.54, P < 0.001). Findings of this meta-analysis do not substantiate a positive effect of CPAP on glucose metabolism in people with T2DM and coexisting OSA. Future large-scale clinical trials with a longer treatment duration and better CPAP compliance are warranted.